2012
DOI: 10.1002/hep.25771
|View full text |Cite
|
Sign up to set email alerts
|

Race- and gender-related variation in natural killer p46 expression associated with differential anti-hepatitis c virus immunity

Abstract: Background Major racial and gender differences have been documented in the natural history and treatment responses of chronic hepatitis C virus (HCV) infection, however, potential mechanisms have remained enigmatic. We hypothesized that racial- and gender-related differences in NK cell populations may explain altered natural history and treatment responses. Methods Our study cohort consisted of 29 African-American (AA, 55% male) and 29 Caucasian-American (CA, 48% male) normal uninfected control subjects. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 31 publications
3
50
0
Order By: Relevance
“…The NKp46-rich intrahepatic NK cell population demonstrated an increased activation compared to the NKp46-poor population as marked by degranulation (CD107a increased, p=0.006; figure 3D, left panel panel; intracellular granzyme B decreased, p=0.01; figure 3D, right panel). It has recently been demonstrated that the unknown ligand for NKp46 in HCV infection is expressed in vitro by a hepatoma cell line transfected with the JFH-1 HCV strain 18. This finding suggests that NKp46 + NK cells have the potential to be activated directly by HCV-infected hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The NKp46-rich intrahepatic NK cell population demonstrated an increased activation compared to the NKp46-poor population as marked by degranulation (CD107a increased, p=0.006; figure 3D, left panel panel; intracellular granzyme B decreased, p=0.01; figure 3D, right panel). It has recently been demonstrated that the unknown ligand for NKp46 in HCV infection is expressed in vitro by a hepatoma cell line transfected with the JFH-1 HCV strain 18. This finding suggests that NKp46 + NK cells have the potential to be activated directly by HCV-infected hepatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…In co-culture experiments, it was shown that NK cells inhibit HCV replication by secreting IFNγ 55,56 . In particular, NKp46 high NK cells efficiently suppressed HCV replication 57,58 . However, the contribution of NK cells to HCV control in vivo during acute HCV infection has not yet been clearly defined.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…TLR stimulation of purified NKp46 hi is associated with increased transcription of cytotoxicity-related genes as compared with NKp46 lo counterparts. Two recent studies (76,77) with further discussion in an editorial (78) highlight that NKp46 hi NK cells (or ligation with an agonist NKp46 antibody) have increased anti-HCV activity in vitro, a process mediated by IFN-γ; accordingly, intrahepatic accumulation of NKp46 hi NK cells is inversely correlated with HCV RNA levels (77). An inverse correlation also exists with the stage of fibrosis and ex vivo intrahepatic NKp46 hi frequencies; in vitro, blockade of NKp46 reduces NK cell-mediated killing of human hepatic stellate cells (HSCs), implicating potentially important antifibrotic roles (77) for this population of NK cells (Figure 2).…”
Section: Figurementioning
confidence: 99%
“…NKp30, which is induced by IL-2, is most highly expressed on the NK and NKT cells of exposed, uninfected subjects (70). The NKp46 receptor is considered the major human natural cytotoxicity receptor involved in NK cell-mediated killing (72,73) and is more highly expressed on the NK cells of women and people of mixed European descent (i.e., populations known to demonstrate higher rates of spontaneous resolution of HCV infection) (74)(75)(76). NKp46 ligand expression is induced on hepatocytes following HCV infection (76), although whether this represents a specific HCV component or an unspecific stress response is not yet clear.…”
Section: Figurementioning
confidence: 99%